Histopathological and molecular effects of microplastics in Eisenia andrei Bouché - Rodriguez-Seijo, A. (2016)
The ocean has been assumed as the main sink of microplastics (MPs), however, soils may also receive MPs from different sources and through different pathways, which may affect the biota and their role in soil functions. To the best of our knowledge, only one study, until now, reported the effects of MPs on the survival and fitness of soil organisms (Lumbricus terrestris). In our study, epigeic earthworms, of the species E. andrei, were exposed to different concentrations of MPs (0, 62.5, 125, 250, 500 and 1000 mg/kg soildw) in an OECD artificial soil and tested for reproduction, survival and growth of adults, following a standard protocol. The size of the polyethylene MPs to which earthworms were exposed ranged between 250 and 1000 μm. No significant effects were recorded on survival, number of juveniles and, in the final weight of adult earthworms after 28d of exposure, to the different concentrations of MPs. Nevertheless, FTIR-ATR of earthworms and histopathological analysis of the gut provided evidences of damages and immune system responses to MPs.